Controlled synthesis of copper nanowire - Ding, Xiang (2015)
Copper nanowire has attracted great attention nowadays due to its cost-effective features with outstanding properties. The capability of conducting controlled synthesis to manipulate the morphology is of great interest. In this paper, various parameters were controlled to study the effect of each factor with a hot-injection synthesis method, modified and improved from traditional synthesis methods. Various characterizations were also done to study the morphology and composition in details.